Molecular Mechanisms of Fanconi Anemia - Ahmad, Shamim; Kirk, Sandra (Medical Intelligence Unit, 2006)
Molecular Mechanisms of Fanconi Anemia will give research students a platform for further investigation, and act as a source of information regarding experimental design. Clinicians will find this title useful for its comprehensive description of Fanconi Anemia and information on the latest molecular theories underlying its causes.